PERTUMBUHAN DAN PARAMETER GENETIK UJI KETURUNAN SENGON (Falcataria moluccana) DI CIKAMPEK, JAWA BARAT - Yayan Hadiyan (Jurnal Pemuliaan Tanaman Hutan, 2010)
Genetically improved seed is one of the important factors in producing a high volume increment of sengon (Falcataria moluccana (Miq.) Barneby & J. W. Grimes) Plantation forest in Indonesia. A progeny test of sengon was established at Cikampek West Java in 2008. The plot was arranged in a randomized complete block design, consisting of 80 families, 4 tree line plot and 6 blocks. At 6 and 12 months of age the progeny test was measured for stem diameter and  height growth. Seed source and family had significant effect on both stem diameter and tree height at six months old, but the seed source did not have significant influence on growth at one year old. Heritability estimate for stem diameter was low (h2i = 0.07) while that of height was moderate (h2i = 0.10). Genetic correlation between diameter and height was strong (rg = 0.90), while age-age correlation for diameter (-0.05)  and height (0.04) were low.